Power asymmetries in global governance for health: a conceptual framework for analyzing the political-economic determinants of health inequities - Alexander Kentikelenis; Connor Rochford (BMC, 2019)
Abstract Background Recent scholarship has increasingly identified global power asymmetries as the root cause of health inequities. This article examines how such asymmetries manifest in global governance for health, and how this impacts health outcomes. Results We focus on the political-economic determinants of global health inequities, and how these determinants operate at different levels of social action (micro, meso, and macro) through distinct but interacting mechanisms. To clarify how these mechanisms operate, we develop an integrative framework for examining the links between global neoliberalism-the currently dominant policy paradigm premised on advancing the reach of markets and promoting ever-growing international economic integration-and global health inequities, and show how these mechanisms have macro-macro, macro-meso-macro, and macro-micro-macro manifestations. Conclusions Our approach enables the design of theoretically-nuanced empirical strategies to document the multiple ways in which the political economy entrenches or, alternatively, might ameliorate global health inequities.